Animal genetic resources and economic development: issues in relation to economic valuation - Rege, J.E.O.; Gibson, John P. (Elsevier, 2003)
The world's domestic animal breeds represent an important resource for economic development and livelihood security. Extensive genetic diversity in these breeds allows the existence of livestock in all but the most extreme environments globally, providing a range of products and functions. Unfortunately, a large number of breeds have been lost and many more are at risk of loss. An important research and development goal is the systematic evaluation of breeds in production systems where they arc typically found, quantitative assessment of the genetic diversity they possess, the definition of relationships amongst breeds and the implementation of programmes for their effective management, including development of policies and strategies for conservation and sustainable utilisation. The key issues of threats to livestock genetic resources, justification for conservation, conservation strategies, priority-setting for conservation are summarised. The potential contribution of economic valuation in ensuring equitable sharing of benefits derived from domestic animal genetic resources (AnGR) is also discussed. Decisions will be required about which breeds are of highest priority, and which conservation or management options represent optimal use of resources for diversity conservation. There is urgent need for the development and application of economic and policy analysis tools to aid rational decision-making in the management of the global domestic AnGR.